MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DENGAN MENGGUNAKAN METODE DEMONSTRASI PADA SISWA KELAS V SD NEGERI 066656 SEMBADA KECAMATAN MEDAN SELAYANG - Siregar, Hotma Tiolina (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
Research carried out this is classroom action research (PTK) using the method of demonstration in science subjects. This study aims to determine the conduct of the study and improvement of student learning outcomes on the subject of Qualities of Light. Student learning outcomes in classical obtained 60.52% of students who complete and incomplete 39.48%, average value of student learning outcomes in the first cycle, namely 63.94, student learning outcomes the first cycle is not maximized, and thus continued in The next cycle. The results of the study on the implementation of the second cycle result of learning on the teachers activities a value of 78.5 with both categories, while the activity of students is 86 in both categories. The results of student learning in the classical obtained 86.84% of students who complete and incomplete 13.16%, average value of student learning outcomes in the second cycle is 76.57. Key Word: Learning Results, Methods Demonstration, IPA.